Prevalence of'healthy lifestyle'in Chinese adults - Zhu, N; Zhou, M; Yu, C; Guo, Y; Bian, Z; Tan, Y; Pei, P; Chen, J; Chen, Z; Lyu, J; Li, L; China Kadoorie Biobank Collaborative Group (Chinese Medical Journals Publishing House, 2019)
Objective To examine the prevalence of a healthy lifestyle in the China Kadoorie Biobank (CKB) of 0.5 million adults from ten areas across China. Methods After excluding participants with self-reported histories of coronary heart disease, stroke or cancer, a total of 487 198 participants at baseline (2004-2008) and 22 604 participants at resurvey (2013-2014) were included in the analysis. A healthy lifestyle was defined as nonsmoking or having stopped for reasons other than illness; alcohol drinking ≺25 g/day (men)/ ≺15 g/day (women); diet rich in vegetables, fruits, legumes and fish, and low in red meat; upper quarter of the physical activity level; body mass index of 18.5-23.9 kg/m2; and waist circumstance ≺85 cm (men)/80 cm (women). We calculated healthy lifestyle scores (HLS) by counting the number of healthy lifestyle factors, with a range from 0 to 6. Results At baseline, the proportion of above five healthy lifestyle factors (except physical activity) was 70.6%, 92.6%, 8.7%, 52.6% and 59.0%, respectively. The mean HLS was 3.1±1.2. Most participants (81.4%) had 2~4 healthy components, while only 0.7% (0.2% in men and 1.0% in women) of participants had all six healthy lifestyle factors. Participants who were women, younger, more educated and rural residents were more likely to adhere to a healthy lifestyle. At resurvey of ten years later, the mean HLS decreased a bit. Conclusion The prevalence of optimal lifestyle status in Chinese adults was extremely low. Healthy lifestyle level varied greatly among the population with different sociodemographic characteristics and across ten areas in China.